The Influence of Product Quality and Brand Image on repurchase Intention of Halal Cosmetic Products in e-Commerce - M. Rachman Mulyandi; Raynaldi Haryvan Tjandra (Journal of Industrial Engineering & Management Research, 2023)
The purpose of this study is to analyze the relationship between product quality and repurchase intention, to analyze the relationship between brand image and repurchase intention. This research is a type of quantitative research with a causality model. This research method is quantitative, the respondents in this study were 400 cosmetic consumer respondents who were determined by simple random sampling, distributing questionnaires through online questionnaires which were distributed through social media such as Twitter, Instagram and WhatsApp. Data analysis used structural equation modeling (SEM) with smartPLS 3.0 software tools. The online questionnaire was designed using a Likert scale of 1 to 7. The stages of data analysis were validity, reliability and hypothesis testing. The results of data analysis show that product quality has a positive and significant effect on repurchase intention, the higher the quality of the product that meets consumer expectations, the higher the intention to repurchase the product in the future. Furthermore, brand image has a positive and significant effect on repurchase intention. A better brand image such as a pioneer of halal beauty products, a good reputation, and a well-known brand results in a higher repurchase intention for the product.